Efficient Genome Editing of Magnetospirillum magneticum AMB-1 by CRISPR-Cas9 System for Analyzing Magnetotactic Behavior - Chen, Haitao; Zhang, Sheng-Da; Chen, Linjie; Cai, Yao; Zhang, Wei-Jia; Song, Tao; Wu, Long-Fei (Frontiers in Microbiology, 2018)
Magnetotactic bacteria (MTB) are a diverse group of microorganisms capable of using geomagnetic fields for navigation. This magnetotactic behavior can help microorganisms move toward favorable habitats for optimal growth and reproduction. A comprehensive understanding of the magnetotactic mechanism at molecular levels requires highly efficient genomic editing tools, which remain underdeveloped in MTB. Here, we adapted an engineered CRISPR-Cas9 system for efficient inactivation of genes in a widely used MTB model strain, Magnetospirillum magneticum AMB-1. By combining a nuclease-deficient Cas9 (dCas9) and single-guide RNA (sgRNA), a CRISPR interference system was successfully developed to repress amb0994 expression. Furthermore, we constructed an in-frame deletion mutant of amb0994 by developing a CRISPR-Cas9 system. This mutant produces normal magnetosomes; however, its response to abrupt magnetic field reversals is faster than wild-type strain. This behavioral difference is probably a consequence of altered flagella function, as suggested with our dynamics simulation study by modeling M. magneticum AMB-1 cell as an ellipsoid. These data indicate that, Amb0994 is involved in the cellular response to magnetic torque changes via controlling flagella. In summary, this study, besides contributing to a better understanding of magnetotaxis mechanism, demonstrated the CRISPR-(d)Cas9 system as a useful genetic tool for efficient genome editing in MTB.